2019
DOI: 10.1136/bmjopen-2019-030699
|View full text |Cite
|
Sign up to set email alerts
|

Policy addressing suicidality in children and young people: an international scoping review

Abstract: ObjectiveTo map key policy documents worldwide and establish how they address the treatment and care needs of children and young people (CYP) who are suicidal.DesignWe conducted a scoping review to systematically identify relevant key policy documents following a pre-established published protocol.Data sourcesFour databases (CINAHL; Medline; PsycINFO; The Cochrane Database of Systematic reviews) and the websites of key government, statutory and non-statutory agencies were searched. Google and Google Scholar we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A recent review of policies and public guidance on suicide in young people noted that the only consistent recommendation among 35 policy documents was that suicidal children should be treated by a child and adolescent mental health practitioner. 166…”
Section: Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of policies and public guidance on suicide in young people noted that the only consistent recommendation among 35 policy documents was that suicidal children should be treated by a child and adolescent mental health practitioner. 166…”
Section: Guidelinesmentioning
confidence: 99%
“…The UK NICE guidelines recommend against stratification of suicide risk, whereas Joint Commission guidelines in the US endorse determining individuals’ level of suicide risk and a plan to mitigate that risk. A recent review of policies and public guidance on suicide in young people noted that the only consistent recommendation among 35 policy documents was that suicidal children should be treated by a child and adolescent mental health practitioner 166…”
Section: Guidelinesmentioning
confidence: 99%
“…Across the UK, suicide prevention research is under-funded 81 , and given the unique situation in NI, it is vital that suicide prevention research is prioritised. It is crucial that suicide prevention actions in Northern Ireland are delivered across the lifespan; embracing the early years and the school context, championing resilience and emotional literacy 85,86 . In particular, the Troubles' legacy and the transgenerational transmission of trauma need further research to understand ongoing risk.…”
Section: Key Challenges and Opportunities For Suicide Prevention In Northern Irelandmentioning
confidence: 99%
“…Self-harm rates are higher in adolescents from lower socioeconomic groups (1,9). The occurrence rates of these behaviors in children and adolescents are also higher in low-and middle-income countries, but the occurrence is also significant in highincome countries (4,10).…”
Section: Epidemiologymentioning
confidence: 99%
“…A review of several international and national guidelines by Gilmour el al. (2019) concluded that these highlight the adoption of general strategies for the prevention and approach of suicide and selfharm (10). Although they consider young people as a priority population, they do not specifically address this age group (10).…”
Section: Assessmentmentioning
confidence: 99%